The complete chloroplast genome of Plagiorhegma dubia Maxim., a traditional Chinese medicinal herb - Caihong Wang; Ying Wang; Qiong Liang; Tae-Jin Yang; Zhilin Li; Yanjun Zhang (Mitochondrial DNA. Part B. Resources, 2018)
Plagiorhegma dubia Maxim. is a traditional Chinese medicinal herb from Plagiorhegma, Berberidaceae, which is distributed in the northeast of China, Korea, Russia. The complete chloroplast genome is 152,468 bp in length, with large single copy (LSC 82,257 bp) and small single copy (SSC 16,599 bp) regions separated by a pair of inverted repeats (IR 26 805 bp). The genome has a total of 113 genes including 79 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic analysis shows that P. dubia is closely related with Sinopodophyllum hexandrum and Epimedium species. The results are of great implication for the development and utilization of P. dubia and the phylogenetic researches on Berberidaceae.